Clinical manifestations and correction of autonomic dysfunction in children and adolescents - T.P. Borysova; A.E. Abaturov (Zaslavsky O.Yu., 2018)
Current data on etiology, classification and terminology of autonomic dysfunction in children are presented. The article describes the features of clinical manifestations of various forms of disturbances, diagnosis and treatment. The results of experimental and clinical studies of the components of Cratal for children (taurine, hawthorn, motherwort) was shown. The high effectiveness of Cratal for children was shown in the treatment of neurocirculatory and vegetovascular forms of autonomic disorders. This was manifested by a decrease or elimination of clinical manifestations of autonomic disorders, improved homeostasis of autonomic system, indicators of the functional state of the cardiovascular system and cerebral circulation.